Body composition of an elit de jockey team - Argentina flows model - Witriw, Alicia Magdalena; Scarano, Santiago Miguel; Martinez, Natalia; De Feo, Yamila; Arbet, Ailín; Enriquez, Verónica Noelia (Seven Editora, 2023)
Hockey is a team sport with a significant energy expenditure due to the different skills and physical conditions required, so it is common that in sports practice the player wants to increase their muscle mass through the use of exogenous aids such as protein supplements. The present study aimed to determine the body composition according to the food plan carried out and position occupied in the field of play of 14 male hockey players on synthetic turf - between 18 and 30 years old-, of first and second division, of the Club Ferrocarril Mitre of the party of San Martín, province of Buenos Aires, Argentina. The dietary variables presented by the players were taken into account and divided into three groups: Group A: subjects who make a food plan without consumption of supplements. Group B: subjects who carry out a meal plan with protein consumption. Group C: subjects who did not consume protein supplements and begin to do so. The measurements were made by a trained and standardized anthropometrist on two occasions; the first at the beginning of the study and the second eight weeks later using the ENFA method. Significant differences were found in the team with larger skeletal size (p = 0.0001), greater amount of muscle mass (p = 0.0018) and lower amount of fat mass (p = 0.0001) in relation to the Phantom and differences in the somatotype between players who occupy different positions on the playing field. In addition, an increase in muscle mass was observed in group C. (p=0.05) DOI:https://doi.org/10.56238/alookdevelopv1-100